Protection of avian influenza (AI) vaccines for poultry against infection of field isolates A/Chicken/West Java/Smi-Pat/2006 and A/Chicken/West Java/Smi-Mae/2008 under laboratory condition - Risa Indriani; N.l.p.I. Dharmayanti; R.M.A. Adjid (Jurnal Ilmu Ternak dan Veteriner, 2011)
The aim of this research was to study level of protection of avian influenza (AI) commercial vaccines available in Indonesia (subtipe H5N1, H5N2 and H5N9) against infection of HPAI field isolates of A/Chicken/West Java/Smi-Pat/2006 and A/Chicken/West Java/Smi-Mae/2008. There were 7 commercial vaccines used in this study, the each vaccines were injected in to 3 weeks old of layer chichickenen intramuscularly. At 3 weeks after vaccination, ten chichickenens from each group were challenged separately with the A/Chicken/West Java/Smi-Pat/2006 and A/Chicken/West Java/Smi-Mae/2008 isolates intranasaly with dose 106 ELD50 per 0,1 ml per chicken. Ten unvaccinated chicken were included in the challenge test as control. The study demonstrate that the AI vaccines with subtipe H5N1 protected chicken (100%) against virus of A/Chicken/West Java/Smi-Pat/2006 and 90-100% against virus A/Chicken/West Java/Smi-Mae/2008. Viral shedding were not seen by 2 days post challenge. The AI vaccines with subtipe H5N2 protected chicken at 20-30% against virus of A/Chicken/West Java/Smi-Pat/2006 and protected chicken at 70-100% against virus of A/Chicken/West Java/Smi-Mae/2008. Viral shedding still detected at 8 days post challenge. The AI vaccines AI with subtipe H5N9 did not protect chicken (0%) against virus A/Chicken/West Java/Smi-Pat/2006 and protected chicken at 50% against virus A/Chicken/West Java/Smi-Mae/2008. Viral shedding still detected by 8 days post challenge. This study concluded that AI vaccines with subtipe H5N1 are better than other AI subtipe vaccines in preventing HPAI virus A/Chicken/West Java/Smi-Pat/2006 dan A/Chicken/West Java/Smi-Mae/2008 infections under laboratory condition. Key Words: Avian Influenza, Vaccine, Poultry, Chicken